Betalipoproteins and Euglobulin Lysis Time - Cucuianu, M (Thrombosis and Haemostasis, 1966)
Previous enrichment of a plasma with betalipoproteins produce an increase of the quantity of proteins, lipids and fibrinogen precipitated with the euglobulins and a corresponding delay in the lysis time of the euglobulin clot. Unpurified betalipoproteins added to a solution of euglobulins produced a delayed lysis time of the clot obtained by coagulating the mixture with thrombin. Betalipoproteins loose their inhibitory activity when they are previously washed with distilled water; the inhibitors could be detected in the supernatant. Small amounts of the inhibitors of plasminogen activation precipitate with the euglobulins. This process is enhanced by betalipoproteins. It is supposed that the delayed lysis time of the euglobulins obtained from plasma of atherosclerotic patients is due to the increase of the fibrinogen and of the inhibitors precipitated with the euglobulins.